Oxygen therapy for acute myocardial infarction. - Cabello, J; Burls, A; Emparanza, J; Bayliss, S; Quinn, T (2010)
Oxygen (O2) is widely recommended for patients with myocardial infarction yet a narrative review has suggested it may do more harm than good. Systematic reviews have concluded that there was insufficient evidence to know whether oxygen reduced, increased or had no effect on the heart ischaemia or infarct size.